Daphnia enhances relative reproductive allocation in response to toxic microcystis: Changes in the performance of parthenogenetic and sexual reproduction. (April 2020) - Zhou, Qiming; Lu, Na; Gu, Lei; Sun, Yunfei; Zhang, Lu; Huang, Yuan; Chen, Yafen; Yang, Zhou
Abstract: Eutrophication and warming lead to frequent occurrence of cyanobacterial blooms, which significantly impact on zooplankton. Freshwater zooplankton Daphnia adopts two distinct ways of reproduction: asexual (parthenogenetic) reproduction for rapidly reproducing many offspring in favorable environment and sexual reproduction for producing resting eggs as seed bank to survive in harsh environments. Daphnia pulex has worse performance in growth and reproduction under the exposure to toxic cyanobacteria Microcystis aeruginosa and tends to allocate less energy to reproduction in the case of insufficient food. However, the relative reproductive allocation strategy (energy allocation) of D. pulex individuals exposed to toxic M. aeruginosa is still unclear. Here we tested the relative reproductive performance of D. pulex fed on solely Chlorella pyrenoidosa (high quality food) or Chlorella mixed with toxic M. aeruginosa (low quality food), based on the parthenogenetic reproduction (life-history experiments) and sexual reproduction (population experiments). The results showed that under low quality food conditions, D. pulex reproduced fewer offspring which were also smaller and thus led to a reduced absolute output in parthenogenetic reproduction, but produced ephippia in the same size and quantity compared to those cultured under high quality food conditions. However, as the body size of maternal D. pulex cultured under low quality food conditions decreased, the relative reproductive allocation significantly increased in both parthenogenetic and sexual reproduction, compared to those cultured under high quality food conditions. In conclusion, D. pulex tend to allocate relatively more energy to reproduction under Microcystis conditions, which is a reasonable strategy for it to decentralize the risks from low-quality food. Graphical abstract: Image 1 Highlights: Daphnia fed toxic Microcystis decreases absolute output in parthenogernesis. Daphnia produces similar biomass of ephippia under toxic Microcystis conditions. Body size of Daphnia fed toxic Microcystis decreases. Daphnia enhances relative reproductive allocation in response to toxic Microcystis. Daphnia tends to allocate more energy to reproduction under toxic Microcystis. Abstract : Daphnia cultured under low quality food conditions tend to allocate relatively more energy to reproduction.